Common variants of the hepatocyte nuclear factor-4alpha P2 promoter are associated with type 2 diabetes in the U.K. population. - Weedon, M; Owen, K; Shields, B; Hitman, G; Walker, M; McCarthy, M; Love-Gregory, L; Permutt, M; Hattersley, A; Frayling, T (2004)
Hepatocyte nuclear factor (HNF)-4alpha is part of a transcription factor network that is key for the development and function of the beta-cell. Rare mutations in the HNF4alpha gene cause maturity-onset diabetes of the young. A number of type 2 diabetes linkage studies have found evidence of linkage to 20q12-13.1 where the HNF4alpha gene is located. Two recent studies have found an association between four common variants of the alternative P2 promoter region and type 2 diabetes. These variants are in strong linkage disequilibrium, and the minor alleles define one common risk haplotype. In both studies, the risk haplotype explained a large proportion of the evidence of linkage to 20q12-13.1. We aimed to assess this haplotype in a U.K. Caucasian study of 5,256 subjects. We typed two single nucleotide polymorphisms tagging the risk haplotype (rs4810424 and rs2144908) and found evidence of association in both case-control and family-based studies; rs4810424 marginally demonstrated the stronger association with an overall estimated odds ratio of 1.15 (95% CI 1.02-1.33) (P = 0.02). The effect of the P2 haplotype on type 2 diabetes risk is less than in the initial studies, probably reflecting that these studies used 20q12-13.1-linked cases. In conclusion, we have replicated the association of the HNF4alpha P2 promoter haplotype with type 2 diabetes in a U.K. Caucasian population where there is no evidence of linkage to 20q.